Analisis Balik dan Metode Stabilisasi pada Pemantauan Lereng Menggunakan Slope Stability Radar Tambang Pit 2 Banko Barat PT Bukit Asam Tbk - Pranteno, Neci Agus; Yusuf, Maulana; Toha, Taufik (Dinasti Research, 2026)
This study aims to examine the causes of slope instability and to produce a more representative color-zoning threshold-based early warning system on the lowwall slope of Pit 2 Banko Barat. The novelty of this study lies in the preparation of an actual color-zoning threshold developed from specific slope conditions and actual field data, rather than only referring to the general threshold of the ESDM guidelines that use general deformation parameters. This research threshold integrates several key parameters, namely the safety factor (FK), landslide probability, slope deformation from Slope Stability Radar (SSR) monitoring, rainfall, and groundwater level conditions so that it is more sensitive in detecting changes in slope behavior before a landslide occurs. The research method uses a quantitative approach through back analysis by utilizing SSR monitoring data, rainfall, groundwater level, and rock characteristics. The results show that landslides are influenced by the presence of weak layers and slope saturation due to high rainfall of 67.87–189.42 mm. The slope deformation rate reaches 16.3–18 mm/hour which indicates a state of alert to critical. Increased rainfall caused a rise in groundwater levels at the BKGT 105 drilling point to 4.57 m and BKGT 106 to 18.57 m, thereby reducing the shear strength of the rock. The resulting color zoning threshold consists of green zones (<5 mm/day), yellow (5–10 mm/day), orange (≥10 mm/day), and red (>30 mm/day). This system is able to describe the stages of landslide development in more detail and adaptively than general thresholds because it considers the actual geotechnical and hydrogeological conditions of the slope. Mitigation efforts were carried out through slope reshaping, surface water control, and the addition of counterweights at the toe of the slope. The application of color zoning-based thresholds has been proven to improve the accuracy of the early warning system and the effectiveness of landslide mitigation on the lowwall slope of Pit 2 Banko Barat